Corporate Disclosure and Cost of Equity: Case of Malaysian Listed Companies - Mohd Razali, Mohd Waliuddin; Brahmana, Rayenda Khresna; Ganisen, a/l Sinnasamy (2014)
Prior studies argue that information costs firm’s capital due to the information asymmetry, and most of those research papers investigated develop countries. Malaysia, as an emerging market, offers its unique characteristic in terms of financial reporting regulation and is hugely influence by export-oriented firms. Therefore, this research aims to investigate whether information disclosure may affect the cost of equity of firms. We investigate this hypothesis by using all Malaysian listed firms excluding the finance, services, and utilities companies over 3 years period of 2010-2012. We use robust panel regression where the values are based on White robust standard errors that control for heterocedasticity errors. Overall, our findings are consistent with previous research that higher level of disclosure might discount the firm’s cost of equity, suggesting that firms should disclose more information for better cost of capital. At the end of our research, we explain our findings using two perspectives which are: information cost and agency cost.